Lignocellulosic Biomass for the Synthesis of Nanocellulose and Its Eco-Friendly Advanced Applications - Gupta, Guddu Kumar; Shukla, Pratyoosh (Frontiers in Chemistry, 2020)
Nanocellulose is a unique and natural compound extracted from native cellulose using different extraction techniques. Nanocellulose is currently attracting attention due to its excellent properties such as special surface chemistry, exceptional physical and chemical strength, and rich hydroxyl groups for modification. In addition, its significant biological properties, like biodegradability, biocompatibility, and non-toxicity, accompanied by being environmentally friendly, are added advantages. The current review is focused on the lignocellulosic biomass processing methods for nanocellulose production and their usage for eco-friendly and environmental sustainability. We have also described insights into different techniques by which cellulosic materials can be changed into cellulose nanofibers (CNFs) and cellulose nanocrystals (CNCs). Lastly, we further discussed how nano-cellulosic materials are being used in a variety of industries such as the food sector, biomedical hygiene products, health care, water purification, and sensors. In the review, the unique uses of nanocelluloses in the production of nanocomposite materials, like flexible supercapacitor and polymer matrix, toward minimizing the utilization of global fossil energy and environmental pollution are envisaged. Finally, the significant application of nanomaterials in the areas of packaging industries, health and hygienic sector, cosmetics, and other important sectors are discussed. In the aspect of techno-economically feasibility, nano-cellulose-based materials may prove to be outstanding, environment friendly, and mitigate effluent load.